Samuel Pufendorf disciple of Hobbes for a re-interpretation of modern natural law - Palladini, Fiammetta (Early modern natural law: studies & sources, 2020)
Part 1. Pufendorf the Hobbesian -- I The Theory of Obligation -- II Nature of Man and State of Nature: the Doctrine of Sociality -- Part 2. Why Did Pufendorf Pass for an Anti-Hobbesian? -- I Pufendorf's Place in the History of Ethics According to Pufendorf -- II The Role of Cumberland -- III Anti-Hobbesian Aspects of the Elementa -- IV The Barbeyrac Factor